Adverse childhood experiences: Assessing the impact on physical and psychosocial health in adulthood and the mitigating role of resilience. (May 2020) - Ross, Nancy; Gilbert, Robert; Torres, Sara; Dugas, Kevin; Jefferies, Philip; McDonald, Sheila; Savage, Susan; Ungar, Michael
Abstract: Background: More than 2000 studies demonstrate adverse childhood experiences ACEs are universal and that experiencing multiple ACEs increases risk for developing physical and psychosocial health problems in adulthood. A challenge faced by clinicians is identifying those most at risk. Recent evidence suggests socio-ecological resilience may mitigate the consequences ACEs. We hypothesize that integrated assessment of ACEs and resilience might improve identification of those at highest risk. Objectives: We examined ACEs among adults attending a rural family practice clinic and explored associations between ACE, socio-ecological resilience and health. Methods: A cross-sectional survey measured ACEs, resilience, and health in adult patients attending a collaborative family health care centre in Lunenburg, Nova Scotia, Canada. Correlation analyses were used to determine associations between the measures. The impact of socio-economic status, level of education and gender was considered. Results: Two hundred and twenty-six persons participated in this study. Approximately 73 % of participants had experienced at least one ACEs and 31 % experienced 4 or more. Overall with increasing numbers of ACEs prevalence of health problems increased. However, individuals with high resilience scores had lower prevalence of health problems. Regression analyses indicated that the number of ACEs were slightly more important predictor of health issues than level of resilience, though both were important. Social economic status, education level and gender were not significant predictors of the impact of ACEs on person's health. Conclusion: The results suggest integrated assessment for resilience and ACEs may facilitate identification of those at higher risk and in need of preventative intervention.